An effective separation and purification of rutin and scoparone from Herba Artemisiae Scopariae by solid-phase extraction cartridges packed with an ionic liquid-based silica. Issue 16 (2nd November 2017) - Ma, Wanwan; Lee, Yuri; Row, Kyung Ho
ABSTRACT: Five types of ionic liquid-based silica were synthesized as solid-phase extraction (SPE) sorbents for separation and purification of bioactive compounds, that is, rutin and scoparone extracted from Herba Artemisiae Scopariae . The SilprBImCl material with the highest adsorption capacity was selected as the sorbent for SPE packing. Ethyl acetate and water were found to be suitable washing and eluting solvents, respectively. SilprBImCl was then applied to multi-phase extraction, and its superiority as a sorbent over the commercial cartridge was proven with high rutin and scoparone recoveries of 90.5% and 83.9%, respectively. This highlights the potential of ionic liquid-based silica materials applied to SPE and MPE.